Interpersonal curiosity as a tool to foster safe relational spaces: a narrative literature review - Letendre Jauniaux, Mélanie; Lawford, Heather L. (Frontiers in Psychology, 2024)
Interpersonal curiosity (IPC), or the desire for information about others, is a core component of human connection, belonging, security, survival, and flourishing. Current research on leveraging IPC is scarce, making it an overlooked mechanism for building safer relational spaces. This narrative literature review attempts to answer the following questions: How can IPC facilitate safe relational spaces? How can this knowledge be made accessible and actionable for readers working in relational fields or public health? Results from the analysis of 23 articles indicate that IPC can manifest as either a trait or a state. At best, IPC can be a powerful tool for connection. At worst, IPC can lead to non-prosocial behaviors and relational disruptions. Suggestions are provided to harness the potential of IPC to foster quality connection and safer relational spaces.